Sistem “Floating with Floor” pada Pembayaran Kupon Sukuk Tabungan Seri ST-004 Perspektif Maqashid Syariah dan Fiqih Kontemporer: Floating with floor, kupon sukuk, sukuk tabungan, obligasi syari'ah, maqashid syari'ah - Saadah, Siti Zumrotus; Rahayu, Puji (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2024)
This study focused on the doubts investors have about the coupon payment sistem of Sukuk ST-004, specifically the "floating with floor" sistem, which differs from the fixed nature of other sukuk coupon payments. Through this study, the floating with floor system will be peeled off from the corner of the maqashid dimension of shari'ah and contemporary jurisprudence. By using qualitative types of research through a literature approach, as well as data collection with literature studies. The primary source of the data was taken from the government memorandum on Sukuk ST-004, Fatwa DSN MUI, and Flyer ST-004. The secondary source is a classic and contemporary book of fiqh related to sukuk transactions. The data analysis used is deductive analysis. The study concluded that the payment sistem is allowed Islamic rule, because it is equivalent to ujroh which refers to the agreement of both parties. In addition, the ability also refers to the purpose of developing and cultivating property (maqshad al-istitsmâr), as well as the purpose of the at-tadawul of wealth (maqshad al-tadâwul)